Optimizing the Role of Notaries in Digital Property Inheritance: A Comparative Legal Analysis - Sendrawan, Tjhong; Agustina, Rosa; Makarim, Edmon; Nefi, Arman; Ipfelkofer, Josephine Rus Indra Sapti (UI Scholars Hub, 2025)
One of the provisions in inheritance laws regarding the transfer of digital property after someone's death is a relatively new and evolving area of legal consideration. Inheritance laws were developed long before the widespread adoption of digital property, such as cryptocurrencies, non-fungible tokens (NFTs), online accounts, and other forms of digital property. As a result, existing inheritance laws often lack clear guidance on how to control the legal transfer of these digital assets upon the owner's death. This article aims to analyze the legal concept of digital property to be inherited and to provide solutions for current digital property inheritance issues from a notarial perspective. This study conducts a thorough analysis of digital property under inheritance law and how notaries should play a role in digital inheritance matters. A method of doctrinal legal analysis of current national and international laws and regulations pertaining to digital property succession is also employed, as well as comparative legislative studies examining proposed policies across jurisdictions to garner real-world insights into the operational challenges, emerging practices, and pragmatic considerations surrounding notary participation in digital inheritance procedures. Updating inheritance laws to address the transfer of digital property is crucial to protect the rights and interests of individuals, promote legal certainty, and ensure that these valuable assets are properly accounted for and transferred to rightful heirs or beneficiaries. The law of property in the Indonesian Civil Code needs to be immediately adjusted to the development of the digitalization era. This article suggests optimizing the role of notaries to create authentic deeds on digital property inheritance. Keywords: Digital property, inheritance, notary, will.